The microprocessor component, DGCR8, is essential for early B‐cell development in mice. Issue 12 (5th October 2016) - Brandl, Andreas; Daum, Patrick; Brenner, Sven; Schulz, Sebastian R.; Yap, Desmond Yat‐Hin; Bösl, Michael R.; Wittmann, Jürgen; Schuh, Wolfgang; Jäck, Hans‐Martin
Abstract : Through the analysis of a B‐cell specific deleter mouse, we could show that the microprocessor component, DGCR8, is required for preventing apoptosis and inducing differentiation signals in pro‐B cells by processing miRNAs and selected pre‐mRNAs, which controls the abundance of, for example, the proapoptotic factor Bim and Ig μHC. Abstract : microRNAs (miRNAs) are important posttranscriptional regulators during hematopoietic lineage commitment and lymphocyte development. Mature miRNAs are processed from primary miRNA transcripts in two steps by the microprocessor complex, consisting of Drosha and its partner DiGeorge Critical Region 8 (DGCR8), and the RNAse III enzyme, Dicer. Conditional ablations of Drosha and Dicer have established the importance of both RNAses in B‐ and T‐cell development. Here, we show that a cre‐mediated B‐cell specific deletion of DGCR8 in mice results in a nearly complete maturation block at the transition from the pro‐B to the pre‐B cell stage, and a failure to upregulate Ig μ heavy chain expression in pro‐B cells. Furthermore, we found that the death of freshly isolated DGCR8 ‐deficient pro‐B cells could be partially prevented by enforced Bcl2 expression. We conclude from these findings that the microprocessor component DGCR8 is essential for survival and differentiation of early B‐cell progenitors.